A New Approach for the Cooperation between Academia and Industry: An Empirical Analysis of the Triple Helix in East China. (July 2016) - Chen, Feiyu; Wu, Chong; Yang, Weining
The triple helix of university–industry–government relations has been accepted as a significant determiner of innovation. For the economic progress of the industrialised nations, the cooperation between academia and industry is terribly crucial. For the purpose of profit maximisation by means of such cooperation, achieving a healthy and productive cooperation is of vital importance. Science and technology (S&T) cooperation platform is an original cooperative mode in East China, which is similar to the technology transfer office. This article researches the cooperation relation and makes a thorough inquiry of the influence of cooperation on high-tech firms. Based on an investigation of 552 high-tech firms and 56 universities, we found that the high-tech firms can improve economic situation via the cooperation with universities on the platform. Moreover, principal discoveries demonstrate that the economic performance of high-tech firms is positively related with the co-operation projects. Furthermore, with a view to making policies and raising probable improvements to cooperative efficiency between academia and industry, this study also finds that high-tech firms selecting distinct cooperation models on the platform will bring different effects on the economic performance of firms.